Making nature-based solutions climate-ready for the 50 °C world. Issue 123 (September 2021) - Ossola, Alessandro; Lin, Brenda B.
Abstract: Nature-Based Solutions (NBSs) promise a future where natural, human and technical elements help solving many of the issues plaguing cities. Pollution reduction, increased human wellbeing and climate change adaptation are only some of the challenges targeted by NBSs. However, under the warming climate affecting many of the world's cities, most of modern NBSs will be highly impacted by the same climate factors they hope to mitigate. As in the case of extreme temperatures or altered water availability, these factors can impact and cause the failure in the organisms, technical elements and governance structures that NBSs rely upon, thus decreasing performance, reliability and sustainability of these solutions. In this commentary we propose critical considerations related to designing, building and managing " climate-ready" NBSs – defined as local integrated solutions able to cope with or adapt to climate change. We do so by highlighting examples in heat- and drought-stricken areas across Australian cities as they sit at the global forefront of a hotter world. We discuss in detail i) tolerance and adaptability of NBS to new climates, ii) NBS design for weather extremes and climate-safety margins, iii) NBS trialing and prototyping, and iv) planning for " climate-ready " NBSs. In doing so, we highlight caveats and limitations to propose an implementation framework to make NBSs not only work, but succeed, in a hotter urban world; one that sees 50 °C as a critical limit to sustain urban life and nature.